The Relationship between Diaper Usage Duration and the Severity of Diaper Dermatitis in Children Aged 1–24 Months at the Integrated Health Post for Toddlers in the Working Area - Popy Aulia Safitri; Fitriyanti; Nindya Aryanty (Journal of Medical Studies, 2025)
ABSTRACT Background: Diaper dermatitis cases have not been extensively documented despite many cases, particularly those seeking treatment in clinics and hospitals. The causes of diaper dermatitis are multifactorial, and the clinical symptoms that arise are varied. This research aims to investigate the relationship between the duration of diaper usage and the severity of diaper dermatitis. Methods: The primary data comprises demographic characteristics and severity diagnosis, which are directly measured through physical examinations, a checklist based on an adaptation from Stamatas, and a questionnaire. The research sample was determined using purposive sampling techniques, consisting of 40 children aged 1-24 months attending the Integrated Health Post for toddlers in the working area of Putri Ayu Community Health Center, diagnosed with diaper dermatitis. Results: This research is dominated by girls with an age range of 1-6 months. They all use disposable diapers. The most widely used cleaning material is non-alcohol-wet wipes. The respondents' parents were mainly in the age range of 26-35 years. Most respondents wore diapers for ≤ 3 hours; the most common severity level was mild. Based on the Spearman rank correlation test results, a P value of 0.000 was obtained, indicating a significant relationship between the duration of diaper usage and the severity of diaper dermatitis. Conclusion: There is a significant relationship between diaper use duration and diaper dermatitis severity. Keywords: Diaper dermatitis; Duration of diaper use; Risk factors